Sex-Based Correlation and Regression between Body Weight and Morphometric Traits of Jawarandu Goats - Ratna Sholatia Harahap; Winni Liani Daulay; Sarwo Edy Wibowo; Gushairiyanto Gushairiyanto; Eko Wiyanto; Bayu Rosadi; Helmi Ediyanto; Depison Depison (Buletin Peternakan, 2026)
The aims of this study was to explore the relationship between body weight and morphometric characteristics in Jawarandu goats raised in Tanjung Jabung Barat, Provincy Jambi. A total of 40 Jawarandu goats (24 males and 16 females) aged 12-24 months were utilized in this study. The traits recorded in this study included body weight and morphometric characteristic. These morphometric variables were later utilized in correlation, regression, and principal component analysis (PCA) to characterize the multivariate structure of body conformation in both male and female Jawarandu goats. Analysis statistics for all morphometric traits were calculated using IBM SPSS Statistics, Minitab, and RStudio. The result showed that the male Jawarandu goats exhibited superior morphometric performance (P<0.05) compared to females in several parameters, including horn length, muzzle circumference, head length, chest depth, rump height, leg circumference, and tail length. The PCA analysis results showed that the first two principal components were able to explain 61.6% of the total variation in the data, with Dimension 1 (51.4%) as the dominant component, showing a clear gap between male and female individuals. The correlation between body weight and body length in males was very strongly correlated (r = 0.817), whereas in females, the correlation was moderate (r = 0.550). The regression models varied among the combined population, males, and females, indicating sex-based differences in growth patterns and body proportions. This approach is particularly valuable in breeding and livestock management programs, especially in field conditions where direct weighing is often impractical.